Interankle Systolic Blood Pressure Difference Is a Marker of Prevalent Stroke in Chinese Adults: A Cross‐Sectional Study. Issue 1 (14th July 2016) - Guo, Hong; Sun, Fengyu; Zhang, Haiyu; Dong, Lihang; Gu, Xingbo; Tian, Ye
Abstract : This cross‐sectional study carried out from November 2014 to December 2014 aimed to determine whether the interankle systolic blood pressure (SBP) difference is an independent marker of prevalent stroke. Simultaneous four‐limb blood pressure measurements (oscillometric devices) and calculated SBP difference between the lower limbs were collected from 1485 participants aged 35 years and older. Questionnaires about traditional stroke risk factors were completed. Interankle SBP difference ≥7 mm Hg was independently associated with a history of stroke after adjusting for traditional stroke risk factors (odds ratio, 1.64; 95% confidence interval, 1.53–3.59; P =.0123). Net reclassification improvement analysis showed that adding the interankle SBP difference to traditional risk factors improved the predictive ability for stroke risk by 18.5% ( P <.001). In conclusion, an interankle SBP difference ≥7 mm Hg could be an independent marker of stroke history in Chinese adults. It could offer an extra benefit in identifying individuals with risk of stroke beyond conventional clinical features.